THE EFFECT OF COUNSELING USING TOOTH BRUSHING POSTERS ON TOOTH BRUSHING BEHAVIOR CHANGES IN PRESCHOOL CHILDREN AT KINDERGARTEN SANTA MARIA PARE - Erni Rahmawati; Astri Yunita; Fresty Africia; Nirmala KS (Indonesian Health Literacy Journal, 2024)
The prevalence of dental caries aged 0-16 years in Indonesia is very high, namely 90%. Vargas, Crall, and Schneider from the United States reported that 61% of a sample of children aged 6-12 years had at least one primary tooth that had caries or filling. The aim of the research was to determine the effect of counseling using posters on learning to brush the teeth on changes in tooth brushing behavior in pre-school children. The research design was experimental using pre-post group intervention. The research sample was 48 respondents at Kindergarten Santa Maria Pare. The independent variable is education using tooth brushing posters, while the dependent variable of the research is tooth brushing behavior. The research instrument used tooth brushing posters for education and behavioral questionnaires. The analysis test uses the Wilcoxon test. The results showed that there was an influence of counseling using posters on learning to brush your teeth on changes in tooth brushing behavior in pre-school children (p=0.000). Health institutions in UKGS activities can provide education using tooth brushing posters in schools on a regular basis.